2013
DOI: 10.2478/bpasts-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

A surface engineering approach applicable to concrete repair engineering

Abstract: Abstract. The objective of the paper is to analyze the effect of substrate roughness and superficial microcraking upon adhesion of repair systems using concrete surface engineering approach. The results presented in this paper have been obtained within the framework of research projects performed to develop a better understanding of the factors affecting the adhesion of repair materials through a surface engineering approach. Based on the results of investigations, the authors showed that the durability and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…It has been widely demonstrated that it can significantly influence on the microcracking level and surface roughness, substrate saturation level and as a consequence it may affect the bond strength between repair material and concrete substrate [3,[13][14][15][16][17][18]. The effect of surface quality on impact-echo signal was investigated for two groups of concrete substrates ( Table 1).…”
Section: Concrete Substrate Quality and Bond Strength Of Tested Repaimentioning
confidence: 99%
“…It has been widely demonstrated that it can significantly influence on the microcracking level and surface roughness, substrate saturation level and as a consequence it may affect the bond strength between repair material and concrete substrate [3,[13][14][15][16][17][18]. The effect of surface quality on impact-echo signal was investigated for two groups of concrete substrates ( Table 1).…”
Section: Concrete Substrate Quality and Bond Strength Of Tested Repaimentioning
confidence: 99%
“…As presented in [28][29][30][31][32], the tests providing the basis for the methodology were carried out on two 2500 × 2500 mm model concrete Table 1 Synthetic description of 3D laser scanning method [37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Schematic and view of test setup Recorded parameters 1 2 3 The 3D laser scanning method exploits laser triangulation.…”
Section: Short Description Of Tests Providing Basis For Methodologymentioning
confidence: 99%
“…The methodology uses parameters estimated on the concrete substrate layer surface by the latest 3D laser scanning method [37][38][39][40][41][42][43][44][45][46][47][48][49][50] and parameters estimated on the floor surface by the impulse response and impact-echo methods [51][52][53][54][55][56][57][58][59] and ANN.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy --Geodesy -----CCTV ---Impulse response ----Impact echo ---Parallel seismic ---Ultrasonic --Ultrasonic tomography ---Acoustic emission ----Radiographic techniques ---Computer tomography ---Electromagnetic induction -----Radar techniques ---Laser static techniques -----Laser dynamic techniques -----Sclerometric static techniques ----Sclerometric dynamic techniques ----Thermographic passive techniques ----Thermographic active techniques ----Static proof loads -----Dynamic proof In recent years rapid advances in non-destructive 3D optical methods have been made. Using such methods one can obtain a 3D image of the surface of concrete [6][7][8][9][10]. Analysing the image by means of dedicated computer programs one can generate, e.g., the values of 3D roughness parameters in accordance with ISO 25178 [11].…”
Section: Optical Methodsmentioning
confidence: 99%